1998
DOI: 10.1039/a706861a
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic ionophores. Part 18: Ag+ selective trithiabenzena- and dithiabenzenapyridinacyclophanes 1

Abstract: The phase transfer catalysed nucleophilic displacement of 1,3-bis(bromomethyl)benzene, 2-methoxy-5methyl-1,3-bis(bromomethyl)benzene (2) and 1,4-bis(bromomethyl)benzene with 2-mercaptoethanol gives the respective diols 3, 4 and 12 (80-85%), which undergo intermolecular cyclodehydrochlorination with thiodiglycolyl dichloride and pyridine-2,6-dicarbonyl dichlorideؒHCl to provide m-phenylene (7-10) and p-phenylene (13-14) based crownophanes. The single crystal X-ray structures of crownophanes 8 and 13 and their N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The complexing abilities of the macrocycle 10 with the selected metal cations Ag I , Cd II , Cu II , Co II , Hg II , Ni II , Pb II and Zn II were assessed by solvent extraction of the metal chlorides from aqueous solutions into chloroform. The procedure was based on the method used by Kumar et al and Nishimura et al, in their investigation of mixed nitrogen and sulfur/oxygen‐donor cyclophanes 51,52. The extraction results, presented in Table 3, indicate that the macrocycle has poor selectivity and it extracts all the metals appreciably.…”
Section: Resultsmentioning
confidence: 99%
“…The complexing abilities of the macrocycle 10 with the selected metal cations Ag I , Cd II , Cu II , Co II , Hg II , Ni II , Pb II and Zn II were assessed by solvent extraction of the metal chlorides from aqueous solutions into chloroform. The procedure was based on the method used by Kumar et al and Nishimura et al, in their investigation of mixed nitrogen and sulfur/oxygen‐donor cyclophanes 51,52. The extraction results, presented in Table 3, indicate that the macrocycle has poor selectivity and it extracts all the metals appreciably.…”
Section: Resultsmentioning
confidence: 99%
“…During our studies on the development of silver selective ionophores, it has been found that the title compound does both, extracts and transports Ag + picrate selectively than Pb 2+ and other metal ions [sel.ext (Ag + /Pb 2+ ) = 564, sel.^nsp (Ag + /Pb 2+ ) = 80] [7][8][9][10]. Its 1 C-NMR spectrum shows more than one signal for each C atom, it may exist as a mixture of two isomeric structures or may have a highly unsymmetrical structure with two unidentical * Correspondence author (e-mail: geeta.hundal@angelfire.com)…”
Section: Discussionmentioning
confidence: 99%
“…3). Imide carbonyl oxygen O( 1) is H-bonded to carbon C(15) of the methoxy group and aromatic carbon C( 11) of aryl unit B, whereas the oxygens of the bridging carbonyl groups, O(3) and O(4), are H-bonded to the bridging methylene carbons C (8) and C(31), respectively (Table 2).…”
Section: Conformational Analysismentioning
confidence: 99%